The Voices of Empowerment: Students' Perceptions on Reading Aloud and Reviewing Strategies in Extensive Reading Experiences: Reading aloud and reviewing strategies - Nailul Fauziyah; Susanto, Fajar (JET ADI BUANA, 2024)
This study investigates the perceptions of higher education students regarding the effectiveness of reading aloud and reviewing strategies in enhancing their extensive reading experiences. Utilizing qualitative methods, including semi-structured interviews, reflective journals, and document analysis, the research explores the benefits and challenges associated with these practices. The findings reveal that reading aloud significantly improves comprehension and engagement by involving multiple senses, allowing for deeper connection with the text. However, challenges such as performance anxiety and pronunciation difficulties were also identified. Reviewing strategies, such as summarizing, annotating, note-taking, and peer discussions, were found to be effective in reinforcing understanding and fostering active engagement with the text. The study suggests that creating supportive environments, providing pronunciation support, combining reading methods, and incorporating technology can enhance the effectiveness of these strategies. The research offers valuable insights for educators seeking to improve extensive reading practices and highlights areas for future research. By addressing the identified challenges and promoting effective strategies, educators can enhance students' reading experiences, fostering a lifelong love for reading and improving literacy skills.